2006
DOI: 10.1103/physrevlett.97.123901
|View full text |Cite
|
Sign up to set email alerts
|

High-Brightness Injection-Seeded Soft-X-Ray-Laser Amplifier Using a Solid Target

Abstract: We demonstrate the generation of an intense soft-x-ray-laser beam by saturated amplification of high harmonic seed pulses in a dense transient collisional soft-x-ray-laser plasma amplifier created by heating a titanium target. Amplification in the 32.6 nm line of Ne-like Ti generates laser pulses of subpicosecond duration that are measured to approach full spatial coherence. The peak spectral brightness is estimated to be 2 10 26 photons= s mm 2 mrad 2 0:01% bandwidth . The scheme is scalable to produce extrem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
53
0
6

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 118 publications
(61 citation statements)
references
References 19 publications
2
53
0
6
Order By: Relevance
“…As active medium it employs a highly ionized plasma which can be generated by a capillary discharge or by an optical laser pulse focused onto a solid target. While first devices provided radiation with a relatively poor coherence [36], nowadays this issue is overcome and diffraction limited beams in the EUV and soft x-ray range are generated [37,38]. Still, these systems are rather complex and their availability is limited to a few research groups only.…”
Section: E U V a N D S O F T X -R Ay S O U R C E Smentioning
confidence: 99%
“…As active medium it employs a highly ionized plasma which can be generated by a capillary discharge or by an optical laser pulse focused onto a solid target. While first devices provided radiation with a relatively poor coherence [36], nowadays this issue is overcome and diffraction limited beams in the EUV and soft x-ray range are generated [37,38]. Still, these systems are rather complex and their availability is limited to a few research groups only.…”
Section: E U V a N D S O F T X -R Ay S O U R C E Smentioning
confidence: 99%
“…It has been demonstrated that applications such as X-ray microscopy (Hertz et al 2009) or spectroscopy (Vogt et al 2004), which were restricted to synchrotron experiments could be realized. Apart from plasma sources, also other tabletop setups operating with high harmonic generation (Seres et al 2007;Zepf et al 2007) or X-ray lasers (Wang et al 2006) generate Xradiation of high brilliance. Laser plasmas are attractive compact X-ray sources due to their small size, high spatial stability and high brightness, and/or high flux.…”
mentioning
confidence: 99%
“…Images of carbon nanotubes were obtained with 46±2 nm resolution determined by a knife edge test. Continuing development of highly coherent table-top EUV/SXR lasers in the vicinity of 10 nm (Wang et al, 2006) can be expected to enable future holographic imaging only limited by the photoresist resolution. Increasing flux of the EUV and SXR table top lasers opens a perspective in the future for www.intechopen.com Two and Three Dimensional Extreme Ultraviolet Holographic Imaging with a Nanometer Spatial Resolution 323 single shot recording, permitting full field time resolved holographic imaging.…”
Section: Discussionmentioning
confidence: 99%